COARSE-CRYSTALLINE PYRITE OF CENTRAL TIMAN - R.I. Shaybekov; M.Yu. Sokerin; V.G. Kotelnikov; A.Yu. Lysyuk; G.V. Ignatyev; E.M. Tropnikov (Минералогия)
The results of mineralogical, geochemical, X-ray, isotopic and spectroscopic studies of coarse-crystalline pyrite (Kyvvozh Formation, Dimtem’el Creek, Central Timan) are presented. Pyrite is characterized by cubic habit and zonal Co distribution. It contains galena, thorite, zircon, monazite, rutile, chlorite, muscovite, quartz, albite, apatite and calcite inclusions. The unit cell parameter of pyrite vary from 5.4137 ± 0.0002 to 5.4187 ± 0.0010 Å and correspond to an ideal pyrite. The sulfur isotopic composition of coarse-crystalline pyrite of 15.8‰ indicates its formation as a result of epigenetic sulfate reduction.